Neutrophil extracellular traps-related genes contribute to sepsis-associated acute kidney injury - Tang Shaoqun; Yu Xi; Wang Wei; Luo Yaru; Lei Shaoqing; Qiu Zhen; Yang Yanlin; Sun Qian; Xia Zhongyuan (BMC Nephrology)
Abstract Background Neutrophil extracellular traps (NETs) and oxidative stress (OS) may be involved in sepsis-associated acute kidney injury (SA-AKI). The aim of this study was to identify potential regulators which modulate NETs and OS in SA-AKI, and to find potential therapeutic agents. Methods and Materials SA-AKI-related datasets GSE255281 and GSE225192 were downloaded from Gene Expression Omnibus. Molecular subtypes associated with NETs were identified by unsupervised clustering. The OS-related genes were obtained by weighted gene co-expression network analysis. Differentially expressed genes were screened by “limma” package in R. Least absolute shrinkage and selection operator algorithm was applied to identify the hub genes. Additionally, the biological functions of the hub genes were analyzed with single sample gene set enrichment analysis. NetworkAnalyst database was searched to screen the drugs targeting the hub targets. qRT-PCR was used to analyze the expression of key genes in the peripheral blood mononuclear cells (PBMCs) of the patients with SA-AKI and healthy controls. HK-2 cells and human umbilical vein endothelial cells (HUVECs) were induced by lipopolysaccharide (LPS) to construct a SA-AKI model, and the effects of estradiol and (+)-JQ1 on HK-2 cells and HUVECs were evaluated by CCK-8 assays, flow cytometry and OS indices. Results Based on NETs-related genes, SA-AKI samples could be divide into two subgroups, and the differentially expressed genes between two subgroups were associated with OS. In silico analyses identified 13 hub targets. The expression of ECT2 and CHRDL1 in PBMCs of SA-AKI patients was significantly lower than that in control group, and the expressions of PTAFR, CSF3 and FOS were significantly higher. Estradiol and (+)-JQ1, which targeted more of the hub targets with good binding affinity, could increase the viability of HK-2 cells and HUVECs induced by LPS and inhibit apoptosis and OS. Conclusion Formation of NETs, contributes to OS and pathogenesis of SA-AKI. Estradiol and (+)-JQ1, targeting multiple regulators in the formation of NETs, may be potential therapeutic agents for the treatment of SA-AKI. Clinical trial number Not applicable.